Efficacy and safety of vancomycin loading doses in critically ill patients with methicillin-resistant Staphylococcus aureus infection. (March 2021) - Flannery, Alexander H.; Wallace, Katie L.; Rhudy, Christian N.; Olmsted, Allison S.; Minrath, Rachel C.; Pope, Stuart M.; Cook, Aaron M.; Burgess, David S.; Morris, Peter E.
Background: While vancomycin loading doses may facilitate earlier pharmacokinetic–pharmacodynamic target attainment, the impact of loading doses on clinical outcomes remains understudied. Critically ill patients are at highest risk of morbidity and mortality from methicillin resistant Staphylococcus aureus (MRSA) infection and hypothesized to most likely benefit from a loading dose. We sought to determine the association between receipt of a vancomycin loading dose and clinical outcomes in a cohort of critically ill adults. Methods: Four hundred and forty-nine critically ill patients with MRSA cultures isolated from blood or respiratory specimens were eligible for the study. Cohorts were established by receipt of a loading dose (⩾20 mg/kg actual body weight) or not. The primary outcome was clinical failure, a composite outcome of death within 30 days of first MRSA culture, blood cultures positive ⩾7 days, white blood cell count up to 5 days from vancomycin initiation, temperature up to 5 days from vancomycin initiation, or substitution (or addition) of another MRSA agent. Results: There was no difference in the percentage of patients experiencing clinical failure between the loading dose and no loading dose groups (74.8% versus 72.8%; p  = 0.698). Secondary outcomes were also similar between groups, including mortality and acute kidney injury, as was subgroup analysis based on site of infection. Exploratory analyses, including assessment of loading dose based on quartiles and a multivariable logistic regression model showed no differences. Conclusion: Use of vancomycin loading doses was not associated with improved clinical outcomes in critically ill patients with MRSA infection.